Design and Simulation Analysis of the Folding DPF for Agricultural Diesel. Issue 1 (1st July 2022) - Guo, Shihao; Wen, Xiang; Dou, Lizhuang; Kou, Guiyue; Mu, Mingfei
Abstract: According to the demand of diesel particulate filter (DPF) for agricultural machinery diesel, a folding DPF was designed by using metal fiber felt as filter element material. The flow characteristics in the designed DPF are simulated by CFD software Fluent, to optimize the structural parameters of the folding DPF. The results show that the pressure drop increases obviously when the ratio of filter element height to inlet height greater than 2; When keeping the filtering area unchanged, the pressure drops of odd filter layers 5, 7 are smaller than that of even filter layers 4, 6, 8, which can be reduced up to 14%; Increasing the length of the filter element helps to make the velocity distribution more uniform along the radial direction at the rear end of the DPF.